Strategi Pengembangan Potensi Makam Watu Cenik Wonogiri sebagai Wisata Ziarah guna Meningkatkan Kunjungan Wisatawan - Alifah Nurul Hidayat; Situ Asih (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Wonogiri Regency in Central Java Province has great potential for sustainable tourism development, particularly through the integration of nature and religious tourism. This study aims to analyze the development strategy of the Watu Cenik Tomb in Sendang Village as a pilgrimage destination, which involves the historical value of the tomb of the Kyai Solo Sumarto IX family, the natural landscape of the Gajah Mungkur Reservoir, and cultural traditions such as Grebeg Syawalan. Using Richard Butler's Sustainable Tourism theory with the Tourism Area Life Cycle (TALC) model, this study applies a descriptive qualitative method through intensive interviews, observations, and documentation of stakeholders such as tourism managers, local communities, and tourists. The results of the study show that Watu Cenik has the potential to be an attractive pilgrimage destination, but its appeal is not yet optimal, with visits limited to private pilgrimages and the local community. The efforts of BUMDes Sendang Pinilih, such as the construction of homestays, shuttle services, and social media promotion, have increased visitor numbers, but additional facilities such as souvenir kiosks, local culinary offerings, photo spots, tour guides, and infrastructure improvements are still needed to attract more visitors and support the creative economy. The research conclusion emphasizes the importance of intensive digital promotion, integrated tour packages, and stakeholder collaboration to realize sustainable tourism that preserves cultural heritage while improving community welfare. Suggestions for further research include integrating mixed methods with quantitative analysis to measure economic impact and comparisons with similar destinations.